(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article specifies the specificity of the creation of a comic in the G. Horin’s idiostyle. The linguistic means (phonetic, lexico-phraseological) and devices (reduction to absurdity, double interpretation, comparison, opposition) of the comic, which characterize the playwright’s creative manner, are analyzed. It is established that in his works lyricism and subtle humor, psychology and a philosophical view of the world are combined. The mastery of all devices and means of comism, together with the comism of the situation and the comism of the character, create a special Gorin’s idiostyle, which reflects the author’s perception of the world.